2018
DOI: 10.1038/s12276-018-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from adipose-derived stem cells overexpressing Nrf2 accelerate cutaneous wound healing by promoting vascularization in a diabetic foot ulcer rat model

Abstract: Diabetic foot ulcers (DFU) increase the risks of infection and amputation in patients with diabetes mellitus (DM). The impaired function and senescence of endothelial progenitor cells (EPCs) and high glucose-induced ROS likely exacerbate DFUs. We assessed EPCs in 60 patients with DM in a hospital or primary care setting. We also evaluated the therapeutic effects of exosomes secreted from adipose-derived stem cells (ADSCs) on stress-mediated senescence of EPCs induced by high glucose. Additionally, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
261
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(299 citation statements)
references
References 37 publications
2
261
0
1
Order By: Relevance
“…Studies revealed that the exosomes of ASCs (over-expressing Nrf2) have improved wound healing in diabetic foot ulcer rat model [224]. In a seminal report, the exosomes derived from ASC isolated from cancer patient have been partly attributed for their therapeutic effect, indicating that expanded ASC remain unaffected by patient condition [225].…”
Section: Asc Secretome and Its Therapeutic Effectmentioning
confidence: 99%
“…Studies revealed that the exosomes of ASCs (over-expressing Nrf2) have improved wound healing in diabetic foot ulcer rat model [224]. In a seminal report, the exosomes derived from ASC isolated from cancer patient have been partly attributed for their therapeutic effect, indicating that expanded ASC remain unaffected by patient condition [225].…”
Section: Asc Secretome and Its Therapeutic Effectmentioning
confidence: 99%
“…Nrf2 (NF-E2-related factor) is an important transcription factor that maintains redox homeostasis in cells, participates in the development of various diseases, and plays an important role in the regulation of oxidative stress [16,42,45].At the same time, related reports indicate that Nrf2 is involved in the proliferation, differentiation, migration and apoptosis of various types of cells [5,46]. The exosomes of adipose-derived stem cells that highly express Nrf2 can promote the healing of diabetic foot ulcer skin wounds in rats [47,48].In vivo and in vitro experiments, we found that LPS-Exos can activate Nrf2 / HO-1 pathway-related proteins, while reducing in ammation-related proteins, promoting endothelial cell vascularization and collagen synthesis.Interestingly, after treatment with exosome-speci c inhibitors (GW4869), the symptoms improved by LPS-Exos were all reversed.…”
Section: Discussionmentioning
confidence: 99%
“…The cells pretreated with high glucose (HG, 30 mm / L) were used as experimental control group. At the same time, in order to better explore the role of LPS stimulated macrophage exosomes, the experimental group used the combination of exosomes inhibitor (GW4869) [5,[21][22][23] and different concentrations of exosomes to treat cells.…”
Section: Cell Culture and Sample Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…After co-incubation for 24 h with PKH26-labeled ASC-Exos, red fluorescence was localized within the cytosol of HDFs, thus confirming the Exo internalization. Li et al [81] suggested that the pro-healing action of ASC-Exos could be mediated by overexpression of nuclear factor-E2-related factor 2 (Nrf2), a transcription factor with a protective role against oxidative stress [82]. The authors isolated Exos from the CM of ASCs cultured in EGM-2MV medium deprived of FBS and supplemented with serum replacement solution for an additional 24 h. CM was centrifuged at 300× g for 10 min and 2000× g for 10 min to remove cell debris.…”
Section: In Vitro Studiesmentioning
confidence: 99%